2001
DOI: 10.1093/emboj/20.14.3840
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a novel hepatitis C virus protein by ribosomal frameshift

Abstract: Hepatitis C virus (HCV) is an important human pathogen that affects ∼100 million people worldwide. Its RNA genome codes for a polyprotein, which is cleaved by viral and cellular proteases to produce at least 10 mature viral protein products. We report here the discovery of a novel HCV protein synthesized by ribosomal frameshift. This protein, which we named the F protein, is synthesized from the initiation codon of the polyprotein sequence followed by ribosomal frameshift into the −2/+1 reading frame. This rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
288
0
8

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 255 publications
(303 citation statements)
references
References 30 publications
7
288
0
8
Order By: Relevance
“…Extensive site-directed mutagenesis within the core/core11 coding region (18) and radioactive sequencing of the protein synthesized in vitro (19) showed that the production of this novel 16 kDa protein resulted from the initiation of translation at the AUG initiator codon of the polyprotein sequence, followed by a 22/11 ribosomal frameshift in an adenosine (A)-rich region located within core codons 8-11. The p16 protein is known as ARFP (alternative reading frame protein) (17), F (for frameshift) (19) or core11 (to indicate the position of the new open reading frame) protein (18,20).…”
Section: Discovery Of the Core11 Orf/proteinmentioning
confidence: 99%
See 4 more Smart Citations
“…Extensive site-directed mutagenesis within the core/core11 coding region (18) and radioactive sequencing of the protein synthesized in vitro (19) showed that the production of this novel 16 kDa protein resulted from the initiation of translation at the AUG initiator codon of the polyprotein sequence, followed by a 22/11 ribosomal frameshift in an adenosine (A)-rich region located within core codons 8-11. The p16 protein is known as ARFP (alternative reading frame protein) (17), F (for frameshift) (19) or core11 (to indicate the position of the new open reading frame) protein (18,20).…”
Section: Discovery Of the Core11 Orf/proteinmentioning
confidence: 99%
“…The p16 protein is known as ARFP (alternative reading frame protein) (17), F (for frameshift) (19) or core11 (to indicate the position of the new open reading frame) protein (18,20).…”
Section: Discovery Of the Core11 Orf/proteinmentioning
confidence: 99%
See 3 more Smart Citations